Visual Outcome After Sutureless Scleral Fixation of Intraocular Lens: Doi: 10.36351/pjo.v37i1.1141 - Sajid Munir, Muhammad; Ramzan, Muhammad; Arshad, Muhammad; Nazir, Shahid; Rizwan Ullah, Muhammad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the results of sutureless scleral fixation of intraocular lens (IOL) in cases of complicated cataract surgery. Study Design: Interventional case series. Place and Duration of Study: Niazi Medical and Dental College Sargodha from Jan 2018 to Dec 2019. Methods: Twenty-five eyes of 25 consecutive patients were selected for this study. Patients of traumatic cataract with zonular dehiscence, patients who had per-operative complications like PC rent with insufficient capsular bag, and children with subluxated lens of Marfan, Ehler Danlos syndrome were included in this study. After routine investigation all patients were operated under local anesthesia except children, who were operated under general anesthesia. Sclerotomies were made at 3 and 9 o’clock positions with MVR blade. Sutureless scleral fixation of intraocular lens was done. The haptics of lenses were buried in the scleral pockets which were already made at 3 and 9 o‘clock position. Post-operative antibiotics and steroids were given for 8 weeks and patients were followed up for two years. Results: Out of 25, 18 (72%) female patients and 7 (28%) male patients underwent surgery. Most of the patients had previous surgical complications of Posterior capsular rent 15 (60%). Four (16%) patients had eye trauma, three had lens subluxation for pseudo-exfoliation and 3 patients (children) were suffering from Marfan Syndrome. Seventy-two percent patients had visual acuity of more than 6/18, 16% had 6/18 to 6/24 and 12% had 6/24 to 6/60. Conclusion: Properly done suture-less scleral fixation is a safe technique with little chance of IOL dislocation. Key Words: Scleral fixation, Intraocular lens, Cataract.